Lightweight design of the chassis framework for a self-propelled peanut planter in hilly areas based on finite element analysis - Yu, Yan; Yi, Dazhi; Wang, Jiasheng; Tan, Xiaozhi; Wang, Xiaomin; Dong, Weikang; Song, Yushuai (International Journal of Agricultural and Biological Engineering, 2025)
The chassis frame of the self-propelled peanut seeder in hilly and mountainous areas is the main supporting structure of the entire machine, and its weight directly affects the operational performance of the seeder. Therefore, in response to the issues of structural heaviness, strength redundancy, and short endurance of the self-propelled peanut seeder in hilly and mountainous areas, this study aims to reduce the overall weight of the machine, conserve resources, and extend the seeder’s endurance time. The research focuses on the chassis frame of the self-propelled peanut seeder, utilizing SolidWorks for 3D modeling. A finite element model of the chassis frame is established using ANSYS Workbench, followed by modal analysis and static analysis under four different working conditions. Based on sensitivity analysis, design variables for the chassis frame are selected, and the response relationships between these design variables are simulated using the Latin Hypercube Design method combined with the Kriging approximation model. Finally, a multi-objective lightweight design is conducted based on the MOGA algorithm. The results indicate that the optimized chassis frame mass is reduced by 28.9%, while meeting the strength requirements. Field tests indicate that the plant spacing qualification rate is ≥98%; the seeding depth operational performance is stable, with an average qualification rate of seeding depth ≥90%. After lightweight design, the prototype structure is stable and the performance is reliable. The research results can provide reference and theoretical basis for the structural optimization and design of the walking chassis frame of self-propelled peanut planters in hilly and mountainous areas. Keywords: self-propelled peanut planter, chassis framework of the walking platform, multi-objective optimization, lightweight design, finite element analysisDOI: 10.25165/j.ijabe.20251805.9447Citation: Yu Y, Yi D Z, Wang J S, Tan X Z, Wang X M, Dong W K, et al. Lightweight design of the chassis framework for a self-propelled peanut planter in hilly areas based on finite element analysis. Int J Agric & Biol Eng, 2025; 18(5): 117–126.